1991
DOI: 10.1128/aac.35.11.2318
|View full text |Cite
|
Sign up to set email alerts
|

Petite mutagenesis in Saccharomyces cerevisiae by a series of bis-cationic trypanocidal drugs

Abstract: A group of bis-cationic imidazo[1,2-a]pyridinium salts and related compounds, some of which exhibit in vivo trypanocidal activity, have been investigated for induction of petite mutagenesis in Saccharomyces cerevisiae. All of the compounds which are active trypanocides induce mutagenesis. There appears to be a correlation between trypanocidal activity and mutagenic activity which may have its structural origin in the spatial separation of the cationic centers.A series of imidazo[1,2-a]pyridinium and related he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Other respiratory inhibitors, i.e., antimycin A and 2,4-dinitrophenol, were also effective at low concentrations. Ethidium bromide has also been reported to target yeast mitochondria by induction of petite mutants, which are deficient in respiration (27). Ethidium bromide had a marked ability to reduce the ATP pools of organism populations but was quite toxic in the animal model of infection, with little apparent reduction of organism burden at the concentrations used (45).…”
Section: Discussionmentioning
confidence: 99%
“…Other respiratory inhibitors, i.e., antimycin A and 2,4-dinitrophenol, were also effective at low concentrations. Ethidium bromide has also been reported to target yeast mitochondria by induction of petite mutants, which are deficient in respiration (27). Ethidium bromide had a marked ability to reduce the ATP pools of organism populations but was quite toxic in the animal model of infection, with little apparent reduction of organism burden at the concentrations used (45).…”
Section: Discussionmentioning
confidence: 99%
“…This result is in harmony with other investigations in which guanabenz was found to be nonmutagenic in various in vitro tests () and where other N -hydroxyamidinohydrazones were found to be mutagenic (). However, it does not hold in every case that amidinohydrazones are not mutagenic while N -hydroxyamidinohydrazones are because mutagenic activities have also been detected for some amidinohydrazones ( , ). The decrease in the mutagenicity of guanoxabenz in the presence of a metabolizing system could be attributable to the retroreduction to guanabenz even when the conditions of the Ames test (NADPH, pH 7.4) are not optimal for the N -reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Current investigative interest in the mechanism of action of these drugs has focused on binding to the minor groove of DNA and inhibition of topoisomerase (8,10,17,20,22), although other pathways have also been studied (2,3,25). Studies of these drugs with trypanosomes have shown good correlation in the ability of these agents to bind to DNA, induce petite mutants in Saccharomyces cerevisiae, and exert trypanocidal activity in the mouse model (8,12,24). This approach has also been applied to P. carinii and other microbes, but further studies are needed to determine its value for prediction of in vivo activity (9,11,25,27).…”
Section: Discussionmentioning
confidence: 99%